Music Pedagogy in Costa Rican Higher Education: A Critical Approach towars the Decolonization of Teaching-Learning Processes - Espinoza Mora, Juan Carlos (2021)
This text aims at generating a critical review of the pedagogical model that has prevailed in Costa Rica for music education, especially since the so-called cultural reform in the early 1970’s. In the search of alternative educational models, these reflections take stand from a critical perspective to propose a pedagogical epistemology free from the oppressive conditions still found in the Costa Rican music field.